Understanding teachers' perspectives on ChatGPT-generated assignments in higher education - Dhamija, Ankit; Dhamija, Deepika (Journal of Interdisciplinary Studies in Education, 2024)
The rapid integration of artificial intelligence (AI) in education has transformed instructional methodologies and administrative tasks. However, teachers in higher education face challenges, particularly in creating high-quality assignments and rubrics amidst increasing administrative burdens. This study investigates the potential of AI, specifically ChatGPT, in streamlining assignment creation. Through automating aspects of assignment development, AI tools offer support to teachers while maintaining pedagogical integrity. However, empirical investigation is needed to understand perceptions and effectiveness. Using observations and semi-structured qualitative interviews, the study explores teachers' perceptions of AI-generated assignments and their impact on student learning outcomes and engagement. It also examines students' experiences and perceptions, understanding AI's role in enhancing learning experiences and facilitating teacher productivity. The data were analysed by content analysis. Findings suggest that teachers found the usage of ChatGPT helpful in reducing their administrative workload while maintaining academic integrity. Additionally, students embraced attempting the assignments, and doing so contributed to enhancing their subject knowledge. Furthermore, teachers facilitated students by encouraging them to reconsider the problem, persisting in their efforts, and inviting communication and collaboration with peers. The study also discusses the implications for teachers, highlighting AI's transformative potential.